A Simple Defence of Monism - (:unkn) unknown (My University, 2020)
Monists about well-being often appeal to the simplicity of their theories as justification for preferring their theories over rival pluralist theories. Pluralists acknowledge the simplicity of monist theories, but argue that monist theories fail to capture many of the well-being facts, and that pluralist theories are to be preferred on the ground of their greater explanatory power. I present a new argument in this paper defending the simplicity argument given by monists. I first present a sophisticated monism, Intrinsic Attitudinal Hedonism, and argue for it’s initial plausibility. I then present considerations from statistical inference, and show that the pluralist’s appeal to explanatory power is weaker than initially thought. I then present arguments traditionally thought problematic for monist theories, and show that Intrinsic Attitudinal Hedonism (and other equally plausible monist theories), keeps pace with rival pluralist theories. I conclude that while the pluralist does have greater explanatory power, given the considerations from statistical inference and the test cases I discuss, such explanatory power is not great enough to grant preference to pluralist theories, and that the simpler monist theories are still preferable.
Keywords: Explanatory Power; Hedonism; Monism; Pluralism; Simplicity